Method of Creation And Creative Process of Composition “Temuku Aya” | Metode Penciptaan dan Proses Kreativitas Komposisi “Temuku Aya” - I Made Adi Suyoga Adnyana; I Ketut Garwa (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Temuku Aya is a musical composition that raises the visual object of temuku as idea in this composition. This musical composition is an innovative composition with the medium of expressing gamelan selonding as well as several additional instruments, such as trompong semarapagulingan, suling, and rain stik. The instrument used in this composition is an instrument with a pelog seven tone. In the method of creating the project of Temuku Aya, it’s based on the method offered by Roger Session in the book The Creative Process written by Brewster Ghiselin. This method has three steps in the creation of music, such as inspiration, conception, and execution. At the execution step there is a creative prosess that is part of the execution step. To perfect the creative prosess in the project Temuku Aya a creator used step by Mr. I Wayan Berata and Mr. I Ketut Gede Asnawa, the addition of step in the creativity process is carried out to provide clear step in carrying out the creativity process to project. There are three steps from Mr. I Wayan Beratha, such as nguping, menahin, and ngelesin, while the steps from Mr.I Ketut Gede Asnawa is ngungkap rasa. From the steps that became the reference of the creator to form the project of the creativity process in the Temuku Aya composition.